David A. Brading: The First America: The Spanish Monarchy, Creole Patriots and the Liberal State, 1492-1866 - Lindhardtsen, Svend (Tidsskriftet Antropologi, 2019)
David A. Brading: The First America: The Spanish Monarchy, Creole Patriots and the Liberal State, 1492-1866 Anmeldes af Svend Lindhardtsen